Electrode Coating
Patent Information
- Application Number
- JP2023007617
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-01-27
- Filing Date
- 2023-01-20
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2043-01-20
AI Technical Summary
、特に、延長されたサイクル寿命を提供できるということを明確に示す。
Smart Images

Figure 0007633295000001 
Figure 0007633295000002 
Figure 0007633295000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an anode comprising a body comprising or consisting of an electrically conductive material and a protective layer disposed on at least one surface of the body, the protective layer comprising or consisting of silylated cellulose, which may comprise at least one ionically conductive additive, and a solvent that solvates the at least one ionically conductive additive present in the protective layer. The present invention also relates to an electrochemical cell comprising the anode of the present invention, and to a method for coating the surface of an electrically conductive material. [Background technology]
[0002] In order to reduce the negative impact on the global environment, vehicle exhaust gas regulations are being further enforced. Therefore, mobility, especially electric mobility, plays an increasingly important role in avoiding vehicle exhaust gases.
[0003] For many years, lithium-ion batteries have been the most commonly used rechargeable battery in many modern life applications such as laptops, cell phones and other portable devices, and in the case of electric and hybrid vehicles, lithium-ion batteries provide the driving range that is now considered acceptable, thus paving the way for mass market acceptance of electric mobility.
[0004] WO 2020 / 007980 discloses the preparation of a trimethylsilyl cellulose coating containing an ion-conducting additive on the surface of a lithium metal anode.
[0005] Due to the high cost and low availability of lithium, alternatives to lithium are urgently needed, and researchers aim to replace the expensive lithium with other materials that are cheaper, highly abundant, and allow the preparation of rechargeable batteries with higher capacity. Within the last decade, materials such as aluminum, zinc, and magnesium, among others, have shown promise, as they offer better storage capacity per unit volume of charge than lithium. All such materials are readily available in the large quantities that are expected to be needed as electric mobility advances.
[0006] DE 102019219007 A1 describes a process for producing magnesium-based powder materials for use in electrochemical cells, as well as negative electrodes and composite electrodes comprising such magnesium-based powder materials and electrochemical cells comprising such negative electrodes or composite electrodes. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2020 / 007980 Brochure [Patent Document 2] DE 102019219007 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention aims to provide an anode that prevents passivation of the anode surface and improves metal deposition, an electrochemical cell containing the anode, and a method for coating the surface of a conductive material. [Means for solving the problem]
[0009] According to a first aspect, the present invention provides an anode comprising a body comprising or consisting of an electrically conductive material and a protective layer disposed on at least one surface of the body, the protective layer comprising or consisting of silylated cellulose, optionally comprising at least one ion-conducting additive, and a solvent that solvates the at least one ion-conducting additive present in the protective layer.
[0010] A second aspect of the present invention relates to an electrochemical cell comprising an anode of the present invention as described herein, a cathode, a separator interposed between the anode and the cathode, and an electrolyte, wherein a protective layer is disposed on the side of the anode facing the electrolyte.
[0011] A third aspect of the invention relates to a method for coating a surface of an electrically conductive material, in particular a surface of an electrode, with silylated cellulose or silylated cellulose comprising at least one ion-conducting additive, comprising the steps of: (i) cleaning the surface of the electrically conductive material from any natural passivation layer and impurities; (ii) optionally smoothing said cleaned surface; (iii) depositing a solution of silylated cellulose or a solution of silylated cellulose comprising at least one ion-conducting additive onto said surface; and (iv) evaporating the solvent, said electrically conductive material comprising at least one of Mg, Zn, Ca, Al, K and Na.
[0012] In a fourth aspect, the present invention relates to the use of a silylated cellulose, optionally comprising at least one ion-conducting additive, as a protective layer on the surface of an electrically conductive material, in particular on the surface of an anode, wherein the at least one ion-conducting additive present in the protective layer is solvated with a solvent. [Brief description of the drawings]
[0013] [Figure 1] 1 shows a cross section of a magnesium metal battery, particularly a magnesium secondary battery 1, of the present invention. [Diagram 2]FIG. 1 shows a schematic diagram of a silylated anhydroglucose repeat unit in a cellulose molecule according to the present invention. [Diagram 3] 1 shows the delamination and deposition of a symmetric Mg-Mg cell. [Figure 4] The cells with the TMSC salt membrane are shown to exhibit stable performance at much lower polarization. [Diagram 5] 1 shows SEM cross-sectional images of brushed Mg compared to Mg with a TMSC protective layer. [Figure 6] 1 shows an SEM image of a Mg with a deposited TMSC protective layer. [Figure 7] The performance of the protected Mg shows that it is stable even in Cl-free electrolytes. [Figure 8A] The exfoliation and deposition process showing the reversibility of Mg deposition. [Figure 8B] The exfoliation and deposition process showing the reversibility of Mg deposition. [Figure 8C] The exfoliation and deposition process showing the reversibility of Mg deposition. [Figure 9A] The electrode with a Mg powder protective surface and a Pt foil protective surface exhibits a much longer cycle life. [Figure 9B] The electrode with a Mg powder protective surface and a Pt foil protective surface exhibits a much longer cycle life. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The prior art discloses the preparation of a trimethylsilyl cellulose coating containing an ion-conducting additive on the surface of a lithium metal anode. A lithium metal anode containing such a coating can function in an electrochemical cell without a liquid electrolyte.
[0015] In this invention, the inventors have recognized that anodes containing other metals, such as magnesium, can be fabricated using trimethylsilyl cellulose coatings containing ion-conducting additives. Considering the application of other metals, the inventors have found that a solvent is required to solvate the ion-conducting additives in the silylated cellulose. In particular, the solvent solvates the crystals in the layer, and ion conduction takes place on these solvated crystals.
[0016] The anode surface, especially the Mg anode surface, can be protected by silylated cellulose. The pores of the silylated cellulose can be filled with a conductive salt that is solid and seals the pores. The surface is ionically conductive, ensuring ion transport but not allowing any other species to pass through. The present invention provides: Prevents passivation of the anode surface, especially the Mg surface, thus enabling stable performance; Improve the deposition of metals, especially Mg, making it more homogeneous, and / or Allows the use of chlorine (Cl)-free electrolytes, thus eliminating corrosion problems in electrochemical cells, especially Mg electrochemical cells.
[0017] In a first aspect, the present invention provides an anode comprising a body comprising or consisting of an electrically conductive material and a protective layer disposed on at least one surface of the body, the protective layer comprising or consisting of silylated cellulose optionally comprising at least one ion-conducting additive, and a solvent that solvates the at least one ion-conducting additive present in the protective layer.
[0018] According to a preferred embodiment, the conductive material of the anode comprises at least one of Mg, Zn, Ca, Al, K and Na. In a preferred embodiment, lithium is not included. Magnesium is particularly preferred.
[0019] "Magnesium" and "Mg" may be used interchangeably herein.
[0020] The present invention provides protection of metal anode surfaces, especially Mg anode surfaces, with silylated cellulose or cellulose derivatives. The pores of the silylated cellulose, i.e. the protective layer, can be filled with an ion-conducting additive, such as a salt, which seals the pores. The embodiment including the conductive salt is preferred in the present invention.
[0021] The solvent solvates the ionically conductive additive that is added to the silylated cellulose, making the surface ionically conductive and ensuring ion transport, but not allowing the passage of any other species.
[0022] The present invention provides an anode coated as described herein, and an electrochemical cell comprising such an anode. The coating described herein prevents passivation of the anode surface, particularly the Mg surface, which allows for stable performance. In particular, the Mg anode coated as described herein allows for the use of Cl-free electrolytes, thus eliminating corrosion problems in electrochemical cells, particularly Mg electrochemical cells.
[0023] The conductive material of the anode body may be composed of a material selected from any magnesium powder-based material, including magnesium metal, magnesium metal alloys, and magnesium alloy powders. Additional metals that may be included in the magnesium alloys used within the present invention include Zn, Al, Si and / or Mn or any combination thereof, such as Al-Zn or Al-Si. Preferably, the Mg metal alloy or alloy powder according to the present invention does not contain Li. Those skilled in the art will understand that "free" in this context does not exclude unavoidable Li impurities.
[0024] For example, the anode body may be a magnesium foil having a thickness of 1000 μm or less, preferably 500 μm or less.
[0025] According to a particularly preferred embodiment of the anode of the invention, the body consists of the conductive material Mg and the protective layer consists of silylated cellulose.
[0026] The at least one conductive additive may in particular be a salt of the conductive material(s).
[0027] The at least one ion-conductive additive may be present in the protective layer in a weight ratio of ion-conductive additive to silylated cellulose of 1-10, preferably 3-8, and most preferably 5.
[0028] At least one conductive additive comprising one or more salts of the conductive material(s) defined herein may be selected from the group consisting of boron hydride anions, bis(trifluoromethane)sulfonimide anions, bis(fluorosulfonyl)imide anions, chloride anions, (BH4)(NH2) anions, hexafluoroisopropylborate anions, 2-trifluoromethyl-4,5-dicyanoimidazole anions, closo-dodecaborate family anions, pentacyanoborate anions, bis(hexamethyldisilazide) anions, perchlorate anions, bromide anions, iodide anions, B(OR) anions, and the like. x )4 anion, and hexafluorophosphate anion.
[0029] The at least one conductive additive may in particular be a magnesium salt, preferably Mg(BH4)2 (magnesium hydrogen boride), Mg(TFSI)2 (magnesium bis(trifluoromethane)sulfonimide), Mg(FSI)2 (magnesium bis(fluorosulfonyl)imide), MgCl2 (magnesium chloride), Mg(BH4)(NH2), Mg[B(hfip)4]2 (magnesium hexafluoroisopropylborate), Mg(TDI)2 (magnesium 2-trifluoromethyl-4,5-dicyanoimidazole), Mg[RB 12 H 11](magnesium closo-dodecaborate family), MgB(CN)5 (magnesium pentacyanoborate), Mg(HMDS)2 (magnesium bis(hexamethyldisilazide)), Mg(ClO4)2 (magnesium perchlorate), MgBr2 (magnesium bromide), MgI2 (magnesium iodide), Mg(B(OR x )4)2, Mg(PF6)2 (magnesium hexafluorophosphate), or any combination thereof, most preferably Mg(BH4)2, or the corresponding calcium or zinc salts.
[0030] It is particularly preferred that the at least one conductive salt is one or more of a Na-salt or K-salt, preferably the respective nitrate, tetrafluoroborate, perchlorate, hexafluorophosphate, thiocyanate hydrate, trifluoromethanesulfonate, bis(trifluoromethane)sulfonimide, bis(fluorosulfonyl)imide, tetracyanoborate, bis(oxalato)borate, 4,5-dicyano-1,2,3-triazolate or 2-trifluoromethyl-4,5-dicyanoimidazole.
[0031] According to another preferred embodiment, the at least one ionically conductive additive is an aluminum salt, which may preferably be one or more of AlCl3, Al(TFSI)3, Al(PF6)3, Al(FSI)3, Al(ClO4)3, AlBr3, and any combination thereof.
[0032] According to another preferred embodiment, the Mg anode described herein is used in combination with at least one Li-conducting salt, the preferred Li-conducting salt being selected from the group consisting of Li(BH4), LiNO3, LiBF4, LiClO4, LiPF6, LiTf, LiSCN, LiTFSI, LiFSI, LiB(CN)4, LiBOB, LiDCTA, LiTDI, and any combination thereof.
[0033] Any of the conductive salts described herein may be combined, provided the resulting mixture is chemically stable and / or inert.
[0034] The protective layer may have a thickness in the range of preferably 100 nm to 500 μm, more preferably 10 μm to 50 μm, and even more preferably 1 μm to 10 μm.
[0035] For good functionality, the protective layer preferably has high ionic conductivity, but at the same time is impermeable to other battery components.
[0036] The silylated cellulose (also called silylated cellulose) for use in the protective layer of the present invention can in principle be any reaction product of cellulose with a silylating agent. In silylated cellulose, one or more hydroxy groups of the glucose units forming the cellulose are substituted with a silyl group. In principle, up to three hydroxy groups can be substituted. According to the present invention, the silylated cellulose preferably contains 0.5 to 3 silyl groups per glucose unit in the cellulose. 2 to 3 silyl groups per glucose unit are more preferred. The silyl groups may be the same or different -SiR3 groups, in which each R may be the same or different. Preferred residues R are independently selected from the group consisting of alkyl, cycloalkyl, alkenyl, alkoxy, aryl, and alkylaryl. The number of carbon atoms of the alkyl group is 1 to 12 (C1 to 12 The number of carbon atoms in the cycloalkyl group may be 3 to 12 (C3 to C4 alkyl), in particular 1 to 4 (C1 to C4 alkyl). 12 The alkenyl group may have 2 to 12 carbon atoms (C2 to C4). 12 The alkoxy group may have 1 to 12 carbon atoms (C1 to alkenyl). 12 The number of carbon atoms in the aryl group may be 6 to 12 (C6 to C8). 12The number of carbon atoms in the alkylaryl group may be 7 to 13 (C7 to 13 Alkyl residues are particularly preferred, in particular C1-4 alkyl. According to a particularly preferred embodiment, alkyl is methyl.
[0037] The silylated cellulose can be derived from microfibrillated or nanofibrillated cellulose, microcrystalline or nanocrystalline cellulose, or bacterial cellulose. Nanofibrillated cellulose is preferred.
[0038] According to a particularly preferred embodiment, silylated cellulose, especially silylated cellulose-based films are prepared using silylated nanofibrillated cellulose ("TMSC" - trimethylsilylcellulose) and magnesium borohydride in an organic solvent such as tetrahydrofuran, dimethylsulfoxide, propylene carbonate, trichloromethane, glyme or other solvents compatible with Mg. Tetrahydrofuran is especially preferred. For such TMSC salt films as protective layers on conductive materials, especially Mg, dry film thicknesses of 20 μm to 40 μm, especially about 30 μm, are preferred.
[0039] In a preferred embodiment, the solvent that solvates at least one ion-conducting additive present in the protective layer is selected from polar aprotic solvents. Such preferred solvents may be tetraglyme (2,5,8,11,14-pentaoxapentadecane), glyme (1,2-dimethoxyethane), diglyme (1-methoxy-2-(2-methoxyethoxy)ethane), triglyme (1,2-bis(2-methoxyethoxy)ethane), THF (tetrahydrofuran), PC (propylene carbonate), EC (ethylene carbonate), ACN (acetonitrile), DMSO (dimethylsulfoxide), sulfolane (tetrahydrothiophene-1,1-dioxide), DMF (dimethylformamide), NMP (N-methylpyrrolidinone), and most preferably includes or is tetraglyme. Of course, any suitable mixture of such solvents is also within the scope of the present invention.
[0040] A polar aprotic solvent may also be included in the electrolyte in an amount of 10 to 100% by volume, more preferably 30 to 70% by volume, and in the most preferred embodiment about 50% by volume.
[0041] A second aspect of the present invention relates to an electrochemical cell comprising an anode of the present invention as described herein, a cathode, a separator interposed between the anode and the cathode, and an electrolyte, wherein a protective layer is disposed on the side of the anode facing the electrolyte.
[0042] The electrochemical cell according to the invention may comprise a negative current collector on the opposite side of the anode facing away from the electrolyte, and / or a positive current collector on the side of the cathode facing away from the electrolyte. Such current collectors are preferably made of a conductive material that is inert to the materials of the anode and cathode, respectively. According to a preferred embodiment of the invention, the electrochemical cell according to the invention is a magnesium cell, in particular a magnesium secondary cell.
[0043] The negative current collector may, for example, comprise a metal foil, metal mesh or metal strip, where the metal may, for example, be nickel, copper or stainless steel, and the positive current collector may, for example, comprise a carbon coded aluminum foil or mesh.
[0044] As the cathode, in principle, any common material can be used. For example, the cathode may contain magnesium or any other metal insertion compound, sulfur and / or redox active organic compounds, either as a single-phase material or as a mixed material, such as mixed with carbon or other conductive compounds and with a binder. According to a preferred embodiment, the cathode may also be protected with a protective layer as described herein.
[0045] The electrochemical cell of the present invention may include a cathode, a separator immersed in an electrolyte, and a magnesium metal anode with a protective layer disposed between the magnesium metal anode and the separator immersed in the electrolyte.
[0046] The separator may in principle be made of any conventional material suitable for separating the anode and cathode compartments. For example, the separator may comprise a porous membrane that is impregnated with the electrolyte.
[0047] Any suitable electrolyte can be used. The electrolyte can be, for example, a polar solvent with a salt dissolved therein, such as a magnesium salt. However, any other electrolyte material is suitable as well. Preferably, the electrolyte does not contain Cl, thus eliminating corrosion problems in electrochemical cells, particularly Mg cells. Also, in such electrochemical cells without Cl-containing electrolyte, the performance of the Mg anode protected as described herein is stable.
[0048] Of course, it is preferable that the magnesium does not react with the electrolyte medium used.
[0049] The third aspect of the present invention is a method for coating the surface of a conductive material.The method for coating the surface of a conductive material with silylated cellulose or silylated cellulose containing at least one ion-conducting additive is described, for example, in WO2020 / 007980, which is incorporated herein by reference.
[0050] In particular, the method of the invention for coating the surface of a conductive material, such as Mg, in particular the surface of an electrode, with silylated cellulose or silylated cellulose comprising at least one ion-conducting additive comprises the steps of: (i) cleaning the surface of the conductive material from any negative passivation layer and impurities; (ii) optionally smoothing the cleaned surface; (iii) depositing on said surface a solution of silylated cellulose or a solution of silylated cellulose containing at least one ion-conducting additive; (iv) evaporating the solvent; may include:
[0051] Such a method offers an easy direct preparation and simple coating technique that can provide protection for Mg metal, Mg alloys and / or Mg powder based electrodes.
[0052] The adhesion of the coated silyl cellulose-based film on the conductive material, such as the TMSC film on the Mg surface, is very good. The thickness of the film layer can be adjusted. Preferably, the surface of the conductive material is essentially completely covered.
[0053] Before forming the protective layer, the surface to be coated, in particular the magnesium surface, is desirably activated. For this purpose, the surface is cleaned from any passivation layers and impurities in step (i). Activation increases the reactivity of the surface and thus strengthens the adhesion between the magnesium material and the silylated cellulose or the protective layer of silylated cellulose containing at least one ion-conducting additive. Activation can be carried out by extrusion from an ingot or by mechanical scratching of the surface.
[0054] After the cleaning step, in step (ii), the surface can be optionally smoothed, for example by rolling (rolling) with a roller to align the surface (remove irregularities). The surface should be activated and cleaned of native passivation layers and impurities, and finally smoothed, so that the protective layer will adhere well.
[0055] In the subsequent step (iii), a solution of silylated cellulose or a solution of silylated cellulose with at least one ion-conducting additive is deposited on the cleaned and optionally smoothed surface. Thus, silylated cellulose or silylated cellulose and at least one ion-conducting additive are dissolved in a suitable solvent and the surface is contacted with this solution. The deposition of the silylated cellulose or the solution of silylated cellulose with at least one ion-conducting additive can be achieved by different techniques including solution coating, solution casting, spray coating, spin coating, dip coating, electrospinning or by using Langmuir-Blodgett coating techniques. The choice of deposition technique is largely governed by the desired thickness of the protective layer and the size of the surface area desired to be coated. In terms of thickness, the protective layer should be as thin as possible while still effectively protecting the metal electrodes, especially the magnesium metal electrodes. The thickness of the layer affects the flexibility and ion conductivity of the interface protective layer. A high quality protective layer should be smooth, continuous and free of holes or defects that could provide a pathway for deleterious substances from the electrolyte.
[0056] Finally, in step (iv), the solvent is evaporated. Corresponding techniques are known to those skilled in the art.
[0057] In the method of the present invention, the conductive material may be as described above and / or may comprise at least one of Mg, Zn, Ca, Al, K and Na. Mg is preferred.
[0058] In the method of the present invention, the conductive material may be selected from the magnesium metal, magnesium metal alloys and magnesium powder-based materials mentioned above.
[0059] The at least one ionically conductive additive is preferably a magnesium salt, in particular Mg(BH4)2 (magnesium borohydride), Mg(TFSI)2 (magnesium bis(trifluoromethane)sulfonimide), Mg(FSI)2 (magnesium bis(fluorosulfonyl)imide), MgCl2 (magnesium chloride), Mg(BH4)(NH2), Mg[B(hfip)4]2 (magnesium hexafluoroisopropylborate), Mg(TDI)2 (magnesium 2-trifluoromethyl-4,5-dicyanoimidazole), Mg[RB 12 H 11 ](magnesium closo-dodecaborate family), MgB(CN)5 (magnesium pentacyanoborate), Mg(HMDS)2 (magnesium bis(hexamethyldisilazide)), Mg(ClO4)2 (magnesium perchlorate), MgBr2 (magnesium bromide), MgI2 (magnesium iodide), Mg(B(OR x )4)2, Mg(PF6)2 (magnesium hexafluorophosphate), or a combination thereof, and most preferably Mg(BH4)2.
[0060] A fourth aspect of the present invention relates to the use of silylated cellulose, optionally comprising at least one ion-conducting additive, as a protective layer on the surface of an electrically conductive material, in particular on the surface of an anode, wherein the at least one ion-conducting additive present in said protective layer is solvated with a solvent.
[0061] In particular, this aspect of the present invention can be used to coat the surface of any commercially available conductive material, especially anodes commonly used in the art. In a particularly preferred embodiment, the anode material for batteries is coated. The examples and Figures 8 and 9 clearly show that protective coating of magnesium electrodes with silylated cellulose can provide beneficial effects, especially extended cycle life.
[0062] In the methods of use described herein, the conductive material may be selected from magnesium metal, magnesium metal alloys and magnesium powder-based materials as described above, and / or the at least one ion-conducting additive is a magnesium salt, preferably Mg(BH4)2 (magnesium borohydride), Mg(TFSI)2 (magnesium bis(trifluoromethane)sulfonimide), Mg(FSI)2 (magnesium bis(fluorosulfonyl)imide), MgCl2 (magnesium chloride), Mg(BH4)(NH2), Mg[B(hfip)4]2 (magnesium hexafluoroisopropylborate), Mg(TDI)2 (magnesium 2-trifluoromethyl-4,5-dicyanoimidazole), Mg[RB 12 H 11 ](magnesium closo-dodecaborate family), MgB(CN)5 (magnesium pentacyanoborate), Mg(HMDS)2 (magnesium bis(hexamethyldisilazide)), Mg(ClO4)2 (magnesium perchlorate), MgBr2 (magnesium bromide), MgI2 (magnesium iodide), Mg(B(OR x )4)2, Mg(PF6)2 (magnesium hexafluorophosphate), or a combination thereof, most preferably Mg(BH4)2.
[0063] According to the invention, it is particularly preferred that the conductive material is selected from magnesium metal, magnesium metal alloys and, in particular, magnesium powder-based materials, and that the at least one ion-conducting additive is Mg(BH4)2.
[0064] The present invention is further illustrated by Figures 1 to 7 and examples.
[0065] Figure 1 shows a cross-section of a magnesium metal battery of the present invention, in particular a magnesium secondary battery 1. The cell includes a negative electrode current collector 2, a magnesium metal anode 3, an interface protection layer 4 (also referred to herein as a "protection layer"), a separator membrane 5, a positive electrode 6 (cathode), and a positive electrode current collector 7. Figure 1 shows a preferred embodiment of the present invention.
[0066] The negative electrode current collector 2 can be made of any material having electronic conductivity, for example, a metal foil such as nickel foil, copper foil, stainless steel foil, etc., preferably copper foil. It is important that the negative electrode current collector is inactive with respect to the negative electrode 3.
[0067] The magnesium metal anode 3 attached to the negative current collector 2 may be made from magnesium foil as described herein and includes an interfacial protection layer 4 on the side of the magnesium metal anode 3 facing the electrolyte opposite the negative current collector 2. The thickness of the magnesium metal anode 3 should be 1000 μm or less, more preferably 500 μm or less.
[0068] Element 5 represents a battery separator membrane immersed in the liquid electrolyte medium. Such a separator 5 in the context of the present invention is a highly porous membrane that prevents electronic contact between the positive and negative electrodes and may be made, for example, from polyolefin or glassy fibers. The thickness of such a separator 5 should be less than or equal to 300 μm, preferably less than or equal to 100 μm. The protective layer 4 comprises a solvent that solvates at least one conductive additive present. Such solvents are described herein above. It is preferred that magnesium does not react with the electrolyte medium used.
[0069] The positive electrode 6 contacts the separator membrane 5 on the side opposite the negative magnesium anode 3. The positive electrode may be attached directly to the positive current collector 7 using a slurry casting method or by pressing a free-standing positive electrode onto the current collector. The positive current collector 7 may be composed of any electronically conductive material, preferably carbon-coated aluminum foil. The positive electrode 6 may contain any magnesium intercalation compound, sulfur or any polymeric organic compound, either as a single phase material or mixed with carbon or any other conductive compound.
[0070] Figure 2 shows a schematic diagram of a silylated anhydroglucose repeat unit in a cellulose molecule according to the present invention. Cellulose is an organic compound consisting of a linear chain of β(1→4) linked D-glucose units. Cellulose-based materials are well known to those skilled in the art.
[0071] Figure 3 shows the exfoliation and deposition of a symmetric Mg-Mg cell. Using the TMSC salt film, the overpotential is lower and the cycling capability is longer.
[0072] Figure 4 shows that while the unprotected cells show increased polarization and short circuit, the cells with the TMSC salt film show stable performance with much lower polarization. With the TMSC salt film, the overpotential is lower and the cycling characteristics are longer. This effect is more pronounced at higher cycle numbers (longer times).
[0073] Figure 5 shows SEM cross-sectional images of brushed Mg compared to Mg with a TMSC protective layer. The TMSC provides a dense protective film on the Mg surface.
[0074] Figure 6 shows the SEM image of Mg with the deposited TMSC protective layer. The adhesion of the TMSC salt film on the Mg surface is very good. The surface of Mg is completely covered with the TMSC salt film. The thickness of the layer is adjustable.
[0075] Figure 7 shows the performance of protected MgCl - This indicates that the compound is stable even in an electrolyte that does not contain
[0076] 8A-C show the exfoliation and deposition process demonstrating the reversibility of Mg deposition.
[0077] 9A-B demonstrate that electrodes with a Mg powder protection surface and a Pt foil protection surface exhibit a much longer cycle life. EXAMPLES
[0078] Peeling / deposition showing reversibility of Mg deposition An experiment was designed using a UFO type cell as follows: an excess of Mg was deposited on a Pt foil (5000 mAh) and half of this amount (2500 mAh) was peeled off. Then, another 2500 mAh capacity of magnesium was continuously deposited and peeled off.
[0079] Although the peeling and deposition of Mg on the Pt foil is not completely reversible, excess Mg was added in the first cycle, which is due to the passivation of Mg when a fresh magnesium surface is exposed to the electrolyte.
[0080] Two experiments were performed. 1) Bare surface of Mg powder (exposed surface) and bare surface of Pt foil 2) Mg powder protection surface and Pt foil protection surface
[0081] Protection was achieved using silylated cellulose and Mg(BH4)2 as a salt incorporated between the cellulose fibers.
[0082] This experiment shows the quality of the protective layer, i.e. how many cycles it takes to lose 1x excess magnesium. If the degradation is too severe, the experiment will fail after a few cycles (not enough magnesium to get 2500mAh).
[0083] This was observed in the case of a bare surface (see Figure 8). After about 25 cycles, the pre-deposited magnesium washes out, and with each cycle more magnesium is lost than is deposited. Hence, after 100 cycles the capacity is zero.
[0084] Figure 9 shows the same experiment with a protective layer. The cycle life is much longer. The degradation is due to the so-called edge effect. * Although the edges were not protected, the overall protective layer allows for a cell lifespan that is approximately 10 times longer, which undoubtedly demonstrates the technical impact of the present invention. *The edge effect means that the edges of the electrodes are not very well covered by the protective layer. This is a common occurrence in non-optimized experimental cells. This effect could be eliminated if the cell engineering is optimized. [Explanation of symbols]
[0085] 1. Magnesium secondary battery 2 Negative electrode current collector 3. Magnesium metal anode 4 Interface protective layer (protective layer) 5 Separator membrane 6 Positive electrode (cathode) 7 Positive electrode current collector
Claims
1. a body including or consisting of a conductive material; a protective layer disposed on at least one surface of the body, An anode, wherein the protective layer comprises or consists of a silylated cellulose containing at least one ion-conducting additive, and a solvent that solvates the at least one ion-conducting additive present in the protective layer.
2. 2. The anode of claim 1, wherein the conductive material of the anode comprises at least one of Mg, Zn, Ca, Al, K, and Na.
3. 2. The anode of claim 1, wherein the conductive material of the anode body is comprised of a material selected from magnesium metal, magnesium metal alloys, and magnesium powder-based materials, and the anode body is a magnesium foil having a thickness of 1000 μm or less.
4. 10. The anode of claim 1, wherein the at least one ionically conductive additive is a salt of the electrically conductive material.
5. 2. The anode of claim 1, wherein the at least one ion-conducting additive is present in the protective layer in a weight ratio of ion-conducting additive to silylated cellulose of 1-10.
6. The at least one ion-conducting additive is selected from the group consisting of borohydride anion, bis(trifluoromethane)sulfonimide anion, bis(fluorosulfonyl)imide anion, chloride anion, (BH 4 ) (NH 2 ) anion, hexafluoroisopropylborate anion, 2-trifluoromethyl-4,5-dicyanoimidazole anion, closo-dodecaborate family anions, pentacyanoborate anion, bis(hexamethyldisilazide) anion, perchlorate anion, bromide anion, iodide anion, B(OR x ) 4 10. The anode of claim 1, comprising one or more salts of the conductive material comprising an anion selected from the group consisting of an anion, an anion, and a hexafluorophosphate anion.
7. 10. The anode of claim 1, wherein the at least one ion-conducting additive is a magnesium salt.
8. 2. The anode of claim 1, wherein the at least one ion-conducting additive is a Na salt or a K salt.
9. 10. The anode of claim 1, wherein the at least one ion-conducting additive is an aluminum salt.
10. The anode of claim 1 , wherein the protective layer has a thickness in the range of 100 nm to 500 μm.
11. 2. The anode of claim 1, wherein the silylated cellulose contains 0.5 to 3 silyl groups per glucose unit in the cellulose.
12. The silyl groups are the same as the group -SiR 3 or a different group -SiR 3 12. The anode of claim 11, wherein each R is independently selected from the group consisting of alkyl, cycloalkyl, alkenyl, alkoxy, aryl, and alkylaryl.
13. 2. The anode of claim 1, wherein the silylated cellulose is derived from microfibrillated or nanofibrillated cellulose, microcrystalline or nanocrystalline cellulose derivatives, or bacterial cellulose.
14. 11. An electrochemical cell comprising the anode of claim 1, a cathode, a separator interposed between the anode and the cathode, and an electrolyte, wherein the protective layer is disposed on a side of the anode facing the electrolyte.
15. 15. The electrochemical cell of claim 14, wherein the solvent is selected from polar aprotic solvents.
16. 16. The electrochemical cell of claim 15, wherein the polar aprotic solvent is included in the electrolyte in an amount of 10 to 100 volume percent.
17. 15. The electrochemical cell of claim 14, further comprising a negative current collector on an opposite side of the anode facing away from the electrolyte and / or a positive current collector on a side of the cathode facing away from the electrolyte, each of which is made from a conductive material that is inert to the materials of the anode and cathode.
18. 15. The electrochemical cell of claim 14 which is a magnesium secondary battery.
19. 1. A method for coating a surface of a conductive material with a silylated cellulose containing at least one ion-conducting additive and a solvent that solvates the at least one ion-conducting additive, comprising the steps of: (i) cleaning the surface of the conductive material from native passivation layers and impurities; (ii) depositing on the surface a solution in which the at least one ion-conducting additive and the silylated cellulose are dissolved in the solvent; (iii) evaporating a portion of the solvent; The method of claim 1, wherein the conductive material comprises at least one of Mg, Zn, Ca, Al, K, and Na.
20. 20. The method of claim 19, wherein the conductive material is selected from magnesium metal, magnesium metal alloys, and magnesium powder-based materials, and / or the at least one ionically conductive additive is a magnesium salt.
21. The method of claim 20, wherein the step of depositing a solution on the surface in which the at least one ion-conductive additive and the silylated cellulose are dissolved in the solvent comprises solution coating, spray coating, spin coating, dip coating, electrospinning, or Langmuir-Blodgett coating.
22. A method for using a silylated cellulose containing at least one ion-conducting additive as a protective layer on the surface of a conductive material, comprising the steps of: The method of use, wherein the at least one ion-conductive additive present in the protective layer is solvated with a solvent.
23. 23. The use of claim 22, wherein the conductive material is selected from magnesium metal, magnesium metal alloys and magnesium powder-based materials, and / or the at least one ion-conducting additive is a magnesium salt.
Citation Information
Patent Citations
Magnesium powder anodes and electrochemical cells comprising such anodes
DE102019219007A1
Active material for batteries, electrode, nonaqueous electrolyte battery and battery pack
JP2015084320A
Electrochemical batteries containing fibril materials such as fibrilcellulose
JP2016513860A
Secondary battery
JP2018098172A
Modified cellulose fiber, dispersion liquid, porous film, electricity storage element and method of manufacturing porous film
JP2019116705A